Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-45 : 5 . (-3-2x) = 3
=> 5 . (-3-2x) = -45 : 3
=> 5 . (-3-2x) = -15
=> -3-2x = -15 : 5
=> -3-2x = -3
=> 2x = -3 - ( -3 )
=> 2x = 0
=> x = 0 : 2
=> x = 0
\(-45:5.\left(-3-2x\right)=3\)
\(\Leftrightarrow\left(-9\right).\left(-3\right)+\left(-9\right).\left(-2x\right)=3\)
\(\Leftrightarrow27+18x=3\)
\(\Leftrightarrow18x=-24\)
\(\Leftrightarrow x=-\frac{24}{18}=-\frac{4}{3}\)
Vậy \(x=-\frac{4}{3}\)
-45:5.(-3-2x)=3 5.(-3-2x)= -45:3 5.(-3-2x)= -15 -3-2x= -15:5 -3-2x= -3 2x= (-3)-(-3) 2x= 0 x=0:2
a) 2/3 + 1/3(2x-1) =-5
1/3(2x-1) = -5 - 2/3
1/3(2x-1) = -17/3
2x-1 = -17/3 : 1/3
2x-1 = -17
2x = -17 + 1
2x = -16
x = -16 : 2
x = -8
b) 25% .x + 2x = 4
x .( 25%+2 ) = 4
x . 9/4 = 4
x = 4 : 9/4
x = 16/9
( 4x - 5 ) - ( 2x + 3 ) = x
4x - 5 -2x - 3 = x
4x - 2x - x = 5 + 3
x = 8
Vậy x = 8
(2x - 3) : (x + 5) thuộc Z
\(\Leftrightarrow\left(2x-3\right)⋮\left(x+5\right)\)
Ta có: 2x - 3 = 2(x + 5) - 13
Mà \(\hept{\begin{cases}2\left(x+5\right)-13⋮\left(x+5\right)\\2\left(x+5\right)⋮\left(x+5\right)\end{cases}}\)
\(\Rightarrow13⋮\left(x+5\right)\)
\(\Rightarrow x+5\inƯ\left(13\right)=\left\{\pm1;\pm13\right\}\)
x + 5 | 1 | -1 | 13 | -13 |
x | -4 | -6 | 8 | -18 |
Vậy...
\(-45:5x\left(-3-2x\right)=3\)
\(-9x\left(-3-2x\right)=3\)
\(27x+18x^2=3\)
\(\Rightarrow9x+6x^2=1\)
\(\Rightarrow x\left(9+6x\right)=1\)